The Impact of food quality on customer satisfaction and local burger repurchase decisions: Kesan kualiti makanan terhadap kepuasan pelanggan dan keputusan pembelian semula burger tempatan - Abdullah, Umi Nadzirah; Azan, Zaliza; JUmain Amborashang (Jurnal Evolusi, 2024)
The research focuses on predicting customer happiness and desire to repurchase local burgers in Cheras. The study aims to understand the elements that impact satisfaction levels at local burger restaurants and their implications for both consumers and businesses in the area. The findings of the research highlight the importance of food quality, service quality, variety of menu, and cafe atmosphere in shaping customer satisfaction and their likelihood to repurchase. Customers prioritize food quality when choosing a restaurant, considering it as one of the most important factors in their decision-making process. The taste, appearance, and overall excellence of the food product significantly influence customers’ perceptions of satisfaction or dissatisfaction. Service quality is another crucial factor that impacts customer satisfaction. The level of service provided by local burger restaurants has a direct impact on customer satisfaction and their likelihood to repurchase. Additionally, the availability of a variety of menu options and a pleasant and inviting cafe atmosphere contribute to higher levels of customer satisfaction. The research methodology employed quantitative methods, such as data collection through questionnaires, to gather numerical measurements and analyze the data using statistical techniques. This allowed the researchers to develop conclusions based on the data collected. Overall, the research provides valuable insights into the factors that influence customer satisfaction and their desire to repurchase local burgers in Cheras. The findings can help consumers make better-educated decisions about where to dine and assist businesses in improving their offerings to enhance customer satisfaction.